English language speaking anxiety (ELSA) among pre-service TESL teachers in IIUM - Che Nazira Che Mohd Nashir
This research aimed to investigate the level of English Language Speaking Anxiety (ELSA) and the self-assessment of English proficiency of pre-service TESL teachers in IIUM. This research also sought to investigate the differences between English Language Speaking Anxiety (ELSA) scores among pre-service TESL teachers in IIUM at different levels of study, and the relationship between English Language Speaking Anxiety (ELSA) and pre-service teachers' self-assessment of their English proficiency. This research involved 134 participants from TESL undergraduates of KOED IIUM. One instrument was developed by combining two instruments, Second Language Speaking Anxiety Scale (SLSAS) by Woodrow (2003) and Teachers' Self-Reported Proficiency by Chacon (2005). The developed instrument developed for use in the study was called the English Language Speaking Anxiety (ELSA) Scale. The findings indicated that the pre-service TESL teachers showed a higher level of speaking anxiety in social settings than in academic settings of IIUM. Next, the pre-service TESL teachers perceived themselves to be most proficient in reading, followed by writing and listening and least proficient in speaking. There was also a significant finding related to pre-service TESL teachers' levels of speaking anxiety and their year of study, with fourth year pre-service TESL teachers found to be the most anxious. There was a slightly stronger relationship between speaking anxiety and English productive skills (speaking and writing) than receptive skills (reading and listening). Both productive and receptive skills were negatively correlated to speaking anxiety. Finally, there was a relatively stronger negative relationship between English speaking proficiency and the social setting of IIUM than the academic setting of IIUM. These findings imply that speaking anxiety does affect pre-service teachers' oral performance and their English proficiency in general. The implications for students, lecturers and university administration are closely related to the notion of self-efficacy and anxiety, and as such, suitable and appropriate recommendations have been proposed.